Analisis Faktor-Faktor Yang Menyebabkan Kredit Bermasalah Pada PT. BPR Arthaguna Mandiri Kantor Pusat Gadobangkong - Dini Rahayu; Rita Yuniarti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the factors that cause non-performing loans at PT. BPR Arthaguna Mandiri. The method used in this research is descriptive with a qualitative approach. Secondary data collection was obtained from documented sources in the company, namely financial reports, and primary data was obtained from the first source, namely through observation and interviews. The population in this study were 20 credit officers of PT. BPR Arthaguna Mandiri and 15 samples representing credit officer employees. The results showed that the factors causing problem loans at PT. BPR Arthaguna Mandiri which dominates is caused by internal factors where there are deviations from credit granting procedures, inaccurate analysis of the elements and principles of lending and weak supervision of credit granting procedures and oversight of debtors. External factors that cause non-performing loans lie in the use of weak bank supervision by debtors, and the debtor's business sector is unable to generate long-term profits. Keywords: Troubled Loans, Credit Granting Procedures, Rural Banks